Analisis Etnosains dalam Pembelajaran IPA di Madrasah Ibtidaiyah Kecamatan Pal Merah, Kecamatan Kota Baru, dan Kecamatan Telanai Pura Kota Jambi - Maysarah; Nazurty; Eddy Haryanto (Postgraduate, University of Mataram, 2025)
This study analyzes the effect of CTL learning model based on ethnoscience on critical thinking skills and science learning outcomes of elementary school students. Initial observations indicate that students' critical thinking skills still need to be improved, especially in articulating their ideas and understanding. With a quantitative approach, data were collected through standardized research instruments and analyzed statistically. The results of the analysis showed a significant difference between the experimental group taught by CTL model based on ethnoscience and the control group. The F count was 83.267 (p <0.05) for simultaneity between the two, 20.075 (p <0.05) for critical thinking, and 168.644 (p <0.05) for learning outcomes. Ethnoscience that connects traditional knowledge with modern science has been proven to play a strategic role in transforming learning. This approach allows students to construct knowledge by connecting academic concepts and cultural experiences, changing the learning model from conventional to constructivist that develops declarative and procedural knowledge. Learning experiences that are linked to cultural contexts create meaningful learning that enhances students' cognitive and metacognitive capacities. Ethnoscience not only bridges local wisdom and scientific knowledge, but also becomes a catalyst for the development of high-level thinking skills.